А Review of Darren Byler, Terror Capitalism: Uyghur Dispossession and Masculinity in a Chinese City. Durham, NC: Duke University Press, 2022, 296 pp. (Антропологический форум / Forum for Anthropology and Culture, 2023)
The book is a study of the position of the Uyghur population of the Xinjiang Uyghur Autonomous Region through the prism of the effect of technology. The author uses the concept of terror capitalism to show the whole complexity of the Uyghurs’ relations with the authorities and with other ethnic groups, and also amongst each other in everyday life. To this end he identifies three processes which Uyghur men are forced to undergo: digital enclosure, ethnoracial devaluation and deprivation of material possessions. He also proposes three means of coping with life’s difficulties: friendship, minor politics and subtraction.